Perception of Teachers on the Role of Quality Assurance in Curbing Examination Misconduct among Secondary School Students in Nasarawa State, Nigeria - Danladi, Uwelo (American Journal of Social Sciences and Humanities, 2019)
This study derives from the observed huge losses incurred yearly by students, parents, schools, exam bodies and government due to examination misconducts. Two research questions and two null hypotheses had been formulated to guide the investigation. The populace of the study comprised 6,165 teachers, which includes principals that had been made up of 4, 518 males and 1,647 females from 245 senior secondary school in Nasarawa State. The multi-stage stratified random sampling process was used to pick out a sample of 600 teachers consisting of 320 males and 280 females from sixteen (16) senior secondary schools in Nasarawa State. A 17-item structured Likert scale developed by the researcher and validated by specialists was used. The studies questions were answered using descriptive statistics, while the hypotheses were tested with t-test statistics at 0.05 alpha. Results indicated that the two hypotheses had been not rejected because the t-test value of -1.063 and -1.052 for hypotheses 1 and 2 of respectively have been much less than the sig. (2.tailed) values of 0.288. This signified that both male and female teachers, and teachers from city and rural schools had the same perception in curbing examination misconduct among secondary school students in Nasarawa State. Based on the findings, the following recommendations have been made: Government need to provide adequate laboratory apparatus and library for students; teachers have to continually evaluate their students regularly; school principals ought to religiously perform their responsibilities and good enough supervision by the Ministry of Education of the State to curtail examination misconduct in Nasarawa state.